Cross-border partnership – the impact of institutions on creating the borderland communities (the case of Spree-Neisse-Bober Euroregion). Issue 1 (2nd January 2016) - Frątczak-Müller, Joanna; Mielczarek-Żejmo, Anna
Abstract : The aim of the paper is to present the cooperation nets generated as a result of the operation of an organization of a cross-border scope and impact, and such is the Spree-Neisse-Bober Euroregion, and to evaluate and assess their role in creating the bonds among the inhabitants. The main research area is the role that the SNBE plays in creating social connections. The authoresses will pay close attention to: the characteristics of Polish-German relations in the borderland; existing social networks within the frames of created partnerships, and the role of the Euroregion as an institution fostering the development of transborder community. The analysis presented here is the result of the research project "Trust beyond Borders. Sprewa-Nysa-Bóbr Euroregion in Perspective of Integrating Processes in Polish-German Borderland". Conducted in 2013, it used content analysis, survey (800 respondents) and unstructured interviews (70 experts from Poland and Germany) methods.